Controlling the Emission Spectrum of Binary Emitting Polymer Hybrids by a Systematic Doping Strategy via Förster Resonance Energy Transfer for White Emission - Bandar Ali Al-Asbahi; Mohamad S. AlSalhi; Amanullah Fatehmulla; Mohammad Hafizuddin Hj. Jumali; Saif M. H. Qaid; Wafa Musa Mujamammi; Hamid M. Ghaithan (Micromachines, 2021)
Tuning the emission spectrum of both binary hybrids of poly (9,9′-di-n-octylfluorenyl-2,7-diyl) (PFO) with each poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) and poly[2-methoxy-5-(3,7-dimethyl-octyloxy)-1,4-phenylenevinylene] end-capped with Dimethyl phenyl (MDMO-PPV–DMP) by a systematic doping strategy was achieved. Both binary hybrid thin films of PFO/MEH-PPV and PFO/MDMO-PPV–DMP with various weight ratios were prepared via solution blending method prior to spin coating onto the glass substrates. The conjugation length of the PFO was tuned upon addition of acceptors (MEH-PPV or MDMO-PPV–DMP), as proved from shifting the emission and absorption peaks of the binary hybrids toward the acceptor in addition to enhancing the acceptor emission and reducing the absorbance of the PFO. Förster resonance energy transfer (FRET) is more efficient in the binary hybrid of PFO/MDMO-PPV–DMP than in the PFO/MEH-PPV. The efficient FRET in both hybrid thin films played the major role for controlling their emission and producing white emission from optimum ratio of both binary hybrids. Moreover, the tuning of the emission color can be attributed to the cascade of energy transfer from PFO to MEH-PPV, and then to MDMO-PPV–DMP.